Cytochemical characteristics of blood cells from Brazilian tortoises (Testudines: Testudinidae) - Martins, G. S. [UNESP]; Alevi, K. C. C. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP]; Bonini-Domingos, C. R. [UNESP] (Funpec-editora, 2016)
The hematology of wild and captive animals is essential for obtaining details about species and represents a simple method of diagnosing disease and determining prognosis. Few studies have described the morphology of chelonian blood cells, which are more common in sea and freshwater turtle species. Thus, in order to further our understanding and recognition of different chelonian cells types, the present study aimed to describe blood cells from the two species of Brazilian tortoises, Chelonoidis carbonarius and C. denticulatus. Cytochemical analysis of tortoise blood tissue with Panotico, made it possible to describe all the of the chelonian cell types (with the exception of thrombocytes): erythrocytes, agranular leukocytes (monocytes and lymphocytes), and granular leukocytes (eosinophils, heterophils, basophils, and azurophils). These data are of high importance for establishing hematological profiles of Brazilian tortoises and reptiles. Therefore, based on our results and on comparative analyses with data from the literature for other reptile species, we can conclude that the blood cells described for Brazilian tortoises are found in all species of reptiles that have been analyzed thus far, and may be characterized and used as a comparative parameter between different groups to evaluate the health status of these animals.
Keywords: Hematology; Reptiles; Chelonoidis carbonarius; Chelonoidis denticulatus